The Implementation Of The Randai Dance At Sman 1 Basa Ampek Balai Kecamatan Basa Ampek Balai, Pesisir Selatan Regency - Zulmayelti, Zulmayelti; Yahya, Yahya; Efi, Agusti (LANGGAM: International Journal of Social Science Education, Art and Culture, 2022)
This study aims to get an overview of the process of implementing the Randai Dance at SMA Negeri 1 Basa Ampek Balai, Pesisir Selatan Regency. Using a qualitative approach as a research method. The analysis used is descriptive analysis with a logical, empirical approach as evidence to justify the researcher's belief or vice versa to build an analysis or conclusion. The researcher obtained the data as the main instrument through an interview with key informants, field notes, recording devices, and cameras. The research location is SMA Negeri 1 Basa Ampek Balai, Pesisir Selatan Regency. In contrast, research informants, in this case, vary based on the accuracy of the selection of key informants who master the problem with the snowball sampling technique. The results showed that the organizational communication process at SMA Negeri 1 Basa Ampek Balai Pesisir Selatan Regency was understood by various kinds of reasoning, ranging from complex understanding to superficial understanding. Organizational communication here seems to have many obstacles to the effect on the implementation of the Randai Dance.